Builders and Building Tradition of Barbaros as Intangible Cultural Heritage - Sarıbekiroğlu, Şeyma; Kul, Fatma Nurşen; Kul, Fatma Nurşen (İstanbul Teknik Üniversitesi, 2022)
This paper aims to document the traditional builders and their know-how in a particular geography, namely the rural settlement of Barbaros in the Urla district of Izmir, Turkey. It aims to shed light on the actors of the building traditions of Barbaros, the process of knowledge transfer among builders, and the traditional know-how related to local building materials and construction techniques as intangible cultural heritage. The research method of this study includes literature review, site survey, and study of oral history. Literature sources provided the theoretical background and limited information related to the history of Barbaros. To understand the traditional building stock in Barbaros, site surveys were conducted in 2016, 2017, and 2020. An oral history study was done with the last living builders and the relatives of late builders. These narratives provided invaluable information for answering the research questions. The results of the study contribute to the conservation of intangible heritage by recording the know-how of the last bearers of traditional construction in Barbaros. This documented experience can be used in future restoration projects not only in Barbaros but also in surrounding settlements with the same traditional construction features. The results of the study are also remarkable in terms of revealing the importance of oral history in documentation studies.
Keywords: Barbaros; Building masters; Building tradition